Factores predictores de complicaciones infecciosas en pacientes sometidos a prostatectomía (2017)
Objective To determine the factors associated with the development of infectious complications in patients undergoing prostatectomy for benign or malignant prostatic disease in Hospital Universitario Mayor. Materials and methods A descriptive cross-sectional study was conducted between 2012 and 2013 on 866 patients subjected to prostate surgery. Univariate and multivariate analyses were performed using logistic regression analysis of perioperative variables using the statistical analysis program Wizard for Mac. Results A total of 284 patients (32.7%) received preoperative prophylaxis, and 167 (19.3%) patients had permanent urinary catheter. There were 89 (10%) patients with Diabetes Mellitus. Complications were identified in 149 (17.2%) patients, and among these, 59 (65.5%) had a urinary infection, 21 (23.3%) patients had orchiepididymitis, and 10 (11.1%) had a surgical wound infection. In the bivariate analysis the presence of diabetes mellitus was significantly associated with the development of UTI, OR 2.04, P=.025. The presence of asymptomatic bacteriuria was associated with the development of vesicocutaneous fistula (P=.00, OR 1.91), and the occurrence of surgical wound infection (P=.004, OR 12.6). It was found that failure to use preoperative prophylactic antibiotics is associated with the formation of vesicocutaneous fistula (OR 0048 P=.04). Conclusions Diabetes mellitus patients are at increased risk of infectious complications, such as urinary tract infection or orchiepididymitis. The presence of asymptomatic bacteriuria is associated with a higher frequency of surgical wound infection. There was no relationship between patients with permanent urinary catheter use and the development of infectious complications. © 2016 Sociedad Colombiana de Urología